Inverted Nipples—A Case Report - Singh, Gurpartap; Mander, Karamjit Singh; Dhir, Anup (Indian Journal of Plastic Surgery, 1989)
A simple and less time consuming technique was tried in a case and is being described in which the underlying pathology was directly approached. The nipple was released in vertical and horizontal directions. Nipple pedicle was stabilized by nonabsorbable purse-string sutures. Limited horizontal undermining beneath the areola was done sufficient enough to cover the nipple pedicle in order to maintain the sensations and vascularity of the areola.
Keywords: Inversion; nipple; areola; pendulous; purse-string suture; lactiferous ducts